Non-exhaustive test for aerobic capacity determination in swimming rats - de Barros Manchado, Fulvia; Gobatto, Claudio Alexandre; Voltarelli, Fabricio Azevedo; Alice Rostom de Mello, Maria (Natl Research Council Canada-n R C Research Press, 2006)
The aim of this study was to describe a double-bout exercise test for non-exhaustive aerobic capacity determination in swimming rats. Adult rats were Submitted to 4 swimming tests at different intensities (4%, 6%, 7%, and 8% of body mass), with intervals of 48 h between them. Two exercise bouts of equal intensity lasting 5 min were performed, separated by 2 min with blood collection for lactate analysis. For each intensity, delta lactate was determined by subtracting lactate concentration at the end of the first effort from the lactate at the end of the second effort. Individual linear interpolation of delta lactate concentration enabled determination of a null delta, equivalent to the critical load (CL). Maxima) lactate steady state (MLSS) was also determined. The estimated CL was of 4.8% body mass and the MLSS was observed at 100% of CL, with blood lactate of 5.20 mmol/L. At 90%, blood lactate stabilized, with a progressive increase to 110% CL. These results offer a potential determination of aerobic capacity in swimming rats.
Keywords: blood lactate; critical load; double-bout exercise test; maximal lactate steady state